The Influence Of Competency, Digital Transformation, Skills Updating, And Artificial Intelligence On Employee Performance At The Ministry Of Transportation Terminal Type A Tirtonadi Surakarta - Cinthya Wijayanti Hadi Saputri; Ahmad Mardalis (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The development of human resource technology is still needed and utilised because human resources can carry out daily tasks in completing their tasks so that management can run well and smoothly. The purpose of this research is to find out and analyze influence competence, digital transformation, renewal skills and artificial intelligence towards performance employee at the Ministry of Transportation Terminal Type A Tirtonadi Surakarta. renewal skills and artificial intelligence on employee performance at the Ministry of Transportation Terminal Type A Tirtonadi Surakarta. This research method uses quantitative research using sampling techniques, namely random sampling, while the sample studied was 100 respondents from 190 employees. The data collection technique in this study used a questionnaire method with data analysis techniques using a quantitative approach with the help of the statistical analysis programme SEM PLS version 3. The results showed that employee competence had a positive and significant effect on employee performance at the. Digital transformation has a positive and significant effect on employee performance at the. Skills renewal has a positive and significant effect on employee performance. Artificial Intelligence (AI) has a positive and significant effect on the performance of employees in improving efficient and effective employee performance.